The impact of training and development facilities on job commitment among entry-level employees: Bangladeshi RMG perspectives - Pervin, Most. Tahura; Zohora, Fatema Tuz (goodwood publishing, 2023)
Purpose: The study intended to ascertain whether providing training and development facilities positively impacted the job commitment of entry-level garment employees in Bangladesh. Research Methodology: The response rate for the survey was 44.89%, derived from a sample size of 450 data points obtained by a basic random sampling technique. The study employed Microsoft Excel 2007, SPSS 22.0, and AMOS 23.0 to conduct exploratory and confirmatory factor analysis and structural equation modeling to assess the strength and reliability of the suggested research framework. Results: The study revealed a significant enhancement in the level of commitment among lower-level employees in the Bangladeshi garment industry when provided with training and development potential. Limitations: One primary constraint encountered in this study pertained to issues associated with data collection. The target demographic consists exclusively of individuals with lower levels of educational attainment. Allocating funds for research in finance remained a significant area of focus. As a result of these limitations, the survey was unable to gather nationwide data. Contribution: This study is distinctive as it focuses on individuals occupying lower-level positions within the Bangladeshi garment sector, exploring the potential avenues for professional advancement. Practical Implication: The study may benefit Bangladeshi garment firms' HR strategy and training and development plans. Environmental and internal variables can stress workers. Professional progress and quality training will help dedicated workers overcome these challenges. Novelty: The study is unique in two perspectives: the bottom-level employees and the emerging economy like Bangladesh.